Evaluating Mindful With Your Baby/Toddler: Observational Changes in Maternal Sensitivity, Acceptance, Mind-Mindedness, and Dyadic Synchrony - Zeegers, Moniek A.J.; Potharst, Eva S.; Veringa-Skiba, Irena K.; Aktar, Evin; Goris, Melissa; Bögels, Susan M.; Colonnesi, Cristina (Frontiers in Psychology, 2019)
Studies on the effectiveness of mindful parenting interventions predominantly focused on self-report measures of parenting, whereas observational assessments of change are lacking. The present study examined whether the Mindful with your baby/toddler training leads to observed changes in maternal behavior and mother-child interaction quality. Mindful with your baby/toddler is a 8 or 9- week mindful parenting training for clinically referred mothers of young children (aged 0 to 48 months), who experience parental stress, mother-child interaction problems, and/or whose children experience regulation problems. The study involved a quasi-experimental non-random design including a sample of 50 mothers, of whom 21 were diagnosed with a mood disorder (n = 21, 42%), an anxiety disorder (n = 17, 34%), post-traumatic stress disorder (PTSD, n = 6, 12%) or other diagnoses (n = 7, 14%). Mothers completed a parental stress questionnaire and participated in home observations with their babies (n = 36) or toddlers (n = 14) during a waitlist, pretest and posttest assessment. Maternal sensitivity, acceptance and mind-mindedness were coded from free-play interactions and dyadic synchrony was coded from face-to-face interactions. Sensitivity and acceptance were coded with the Ainsworth’s maternal sensitivity scales. Mind-mindedness was assessed by calculating frequency and proportions of appropriate and nonattuned mind-related comments. Dyadic synchrony was operationalized by co-occurrences of gazes and positive facial expressions and maternal and child responsiveness in vocal interaction between the dyad. Coders were blind to the measurement moment. From waitlist to pretest, no significant improvements were observed. At posttest, mothers reported less parenting stress, and were observed to show more accepting behavior and make less nonattuned comments than at the pretest, and children showed higher levels of responsiveness. The outcomes suggest that the Mindful with your baby/toddler training affects not only maternal stress, but also maternal behavior, particularly (over)reactive parenting behaviors, which resulted in more acceptance, better attunement to child’s mental world and more “space” for children to respond to their mothers during interactions. Mindful with your baby/toddler may be a suitable intervention for mothers of young children with (a combination of) maternal psychopathology, parental stress, and problems in the parent-child interaction and child regulation problems.